Implementation of Village Regulation of Peresak No. 5 of 2021 on the Maturity of Marriage Age - Maulida, Baiq Indri Astri; Rispawati, Rispawati; Basariah, Basariah; Yuliatin, Yuliatin (Jurnal Penelitian Medan Agama, 2025)
This study aims to examine the implementation and influencing factors of Village Regulation of Peresak No. 5 of 2021 concerning the Maturation of Marriage Age. Using a descriptive qualitative approach, data were collected through interviews, observations, and documentation, and analyzed using the Miles & Huberman model. The findings indicate that the regulation is implemented through several village government programs, including marriage age maturation efforts, handling child marriage cases, social rehabilitation, and the establishment of the PUP task force. These initiatives have proven effective in reducing child marriage cases from 12 (2018-2020) to 5 (2021-2023), with zero cases recorded in 2024. The supporting factors include increased awareness among village officials about the negative impacts of child marriage and effective communication among stakeholders. Meanwhile, the inhibiting factors are the low public awareness of the regulation's benefits due to limited participation in socialization activities and the persistence of traditional cultural views that normalize child marriage.